2014
DOI: 10.4103/0975-9476.128852
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Cissus quadrangularis Linn. on diabetes induced delayed fetal skeletal ossification

Abstract: Background:Delayed fetal skeletal ossification is one of the known complications of maternal diabetes.Objective:The present study was designed to evaluate the protective role of petroleum ether extract of Cissus quadrangularis (PECQ) on diabetes-induced delayed fetal skeletal ossification.Materials and Methods:Female Wistar rats were rendered diabetic with streptozotocin (STZ, 40 mg/kg, intraperitonial) before mating. After confirmation of pregnancy, the pregnant rats were divided into three groups: normal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…CQ extract was effective against diabetes-induced delayed fetal skeletal ossification, restoring the ossification centers in the neonatal pups of diabetic rats (Sirasanagandla et al, 2014). Several studies showed the capacity of CQ to reduce bone loss, as evidenced by the bone weight gain, density, strength, and calcium content in ovariectomised or orchidectomized animals (Jadhav et al, 2016;Potu et al, 2009).…”
Section: Animal Studiesmentioning
confidence: 99%
“…CQ extract was effective against diabetes-induced delayed fetal skeletal ossification, restoring the ossification centers in the neonatal pups of diabetic rats (Sirasanagandla et al, 2014). Several studies showed the capacity of CQ to reduce bone loss, as evidenced by the bone weight gain, density, strength, and calcium content in ovariectomised or orchidectomized animals (Jadhav et al, 2016;Potu et al, 2009).…”
Section: Animal Studiesmentioning
confidence: 99%